Childhood growth of singletons conceived following intracytoplasmic sperm injection – irrelevance of gonadotropin stimulation - Minger, M. A.; Sommer, G.; Mitter, V. R.; Purtschert, L. A.; von Wolff, M.; Kohl Schwartz, A. S. (Frontiers in Reproductive Health, 2024)
BackgroundIn conventional, gonadotropin stimulated, in vitro fertilization or intracytoplasmic sperm injection (c-IVF/ICSI) growth and development of multiple follicles is induced by gonadotropins, combined with gonadotropin-releasing hormone agonist or antagonist. In recent studies, singletons conceived after c-IVF/ICSI cycles had lower birth weight not only than spontaneously conceived children but also children born after unstimulated natural IVF/ICSI cycles (NC-IVF/ICSI). Lower birth weight is associated with a catch-up growth within the first years of life. Following the Barker hypothesis accelerated growth has been associated with a higher risk of cardiovascular diseases later in life. The aim of the study is to assess, if children conceived with NC-IVF/ICSI have a higher birthweight and therefore do not show a catch-up growth within the first two years. Therefore, we assume that children born after NC-IVF/ICSI have a better long-term cardiometabolic risk profile. Whether the weight- and height gain is comparable to spontaneously conceived children is unknown, since to our knowledge we are the first study to investigate the longitudinal growth of children born after unstimulated natural cycle ICSI (NC-ICSI).Material and methodsWe conducted a single-center, prospective cohort study (2010-2017) including children (n = 139) born after NC-ICSI or c-ICSI treatment. Growth parameters up to 24 months were collected. Standard deviation scores based on growth references were calculated.ResultsThe study included 98 children in the NC-ICSI and 41 children in the c-ICSI group. The median birth weight in NC-ICSI children was 3.4 kg [0.1 standard deviation score (SDS)] compared to 3.3 kg (−0.3 SDS) in c-ICSI children (p = 0.61). Median length at birth was 50 cm in both groups (NC-ICSI (−0.5 SDS), c-ICSI children (−0.8 SDS), p = 0.48). At age 24 months, median weight in NC-ICSI children was 12.2 kg (0.3 SDS) versus 12.2 kg (0.2 SDS) in c-ICSI children (p = 0.82) and median length 87.5 cm (0.1 SDS) versus 88.0 cm (0.4 SDS) (p = 0.43).ConclusionWe found no difference in growth between children conceived after stimulated and unstimulated ICSI. Growth parameters of both treatment groups did not differ from Swiss national growth references (N = 8500). One of the main limitations of our study was the small sample size (N = 139) of complete data sets over time and the high drop-out rate of 49% (68/139). Nevertheless, with the increasing number of children born after IVF/ICSI every year it is of immense importance to search for possibilities to reduce their long-term cardiometabolic risk and we want our data to contribute to this discussion.